Research and development - Bosworth, Derek L.; Wilson, Robert A.; Young, Alison; Royal Statistical Society (Great Britain); Economic and Social Research Council (Great Britain) (London ; New York : Chapman & Hall, 1993)
This study reviews the UK research and development statistics which have become available during the post-World War II period. The subject area covers both government and non-official sources, and includes a wide range of data, such as research and development expenditures and employment figures.
Includes bibliographical references (p. 191-195) and index.
rpm 26/08/16
Loans
Keywords: Research and development contracts; Industrial promotion; Research, Industrial